ETIKA NEGOSIASI DALAM DUNIA KOMUNIKASI DIGITAL KAJIAN PADA PR, DAN ADVERTISING - unasih, febrivsl; Muhammad Nasha Prasetyo; Mohammad Zidan Asyawa; Muhammad Rizki Dwi Yuliyanto; Hari Eko Purwanto (Universitas Muhammadiyah Jakarta, 2025)
This study examines the significance of ethics in negotiation processes in thedigital communication era, particularly in the context of Public Relations (PR) andadvertising. In an era of rapid technological advancement and transformation of socialinteraction, communication now takes place not only face-to-face but also throughdigital platforms such as social media, email, and various online forums. This situationpresents new ethical challenges, where the distinction between right and wrong isbecoming increasingly complex. Using a Systematic Literature Review (SLR)approach, this study analyzed various scientific literature sources from 2020 to 2025related to the theme of ethics in digital negotiations. The articles analyzed came fromindexed journals that discuss advertising ethics, online communication ethics, and PRpractices in the digital environment. This research shows that various ethical issuespersist, such as the spread of deceptive advertisements, child exploitation inadvertising, the use of technologies such as Artificial Intelligence (AI) without clearguidelines, and unclear support from influencers on social media platforms. Thestudy's findings indicate that ethics is a crucial foundation for maintaining public trust,creating a positive corporate image, and avoiding communication crises. Values suchas candor, social responsibility, and transparency are key aspects of good digitalcommunication practices.